ANALYZING THE LOCATION OF THE FAMOUS CITY OF DAWAN AND THE ROUTE OF LI GUANLI'S CONQUEST OF DAWAN - Li Yu Qiao; Hikmatulla Hoshimov; Alisher Aloxunov (Scholars Digest Publishing, 2025)
The war of Tian Ma" refers to the two Han army's attacks on Dawan wars commanded by Li Guangli. This military action not only shocked Dawan and made it pay tribute to Dawan's fine horses to the Western Han Dynasty, but also attacked the Xiongnu's influence in the Western Regions, making it the countries in the Western Regions were powerful in the Western Han Dynasty. However, due to factors such as the long distance, the information about Dawan recorded in Chinese historical materials is fragmented, and the historical records have deviations after the Han and Dawan dynasties changed. The detailed locations of the famous Dawan cities such as "Guishan"（贵山, "Yucheng"（郁城） and "Ershi" (贰师)cannot be determined, and thus Li Guangli's marching route cannot be determined. This article combines historical data, previous research and new results of Central Asian archeology in recent years to discuss and determine the positions of "Yucheng" and "Ershi".
Keywords: Han Dynasty and Dawan War, Ershi City, Mingtepa site, Military Archeology.